2018
DOI: 10.1155/2018/6420314
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Watermarking Method Based on Energy Averaging in Audio Signals

Abstract: Methods based on discrete cosine transform (DCT) have been proposed for digital watermarking of audio signals; however, the watermark is often vulnerable to data compression and signal processing. This paper presents an effective audio watermarking method by energy averaging of DCT coefficients such that an audio signal with watermark is robust to data processing. The method is to divide an audio signal into segments by three parameters defining the segment length, the segment sequence of watermark location, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…On the other hand, the transform domain technique is applied to coefficients obtained as the result of transformation of either a whole audio or the frame of the audio. Some well-known and conventional transform domain techniques are discrete wavelet transform (DWT) [4], discrete cosine transform (DCT) [5], and fast fourier transform (FFT) [6]. Pandey et al [3] presented a method that uses the pseudo-random gray sequence property.…”
Section: Related Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the transform domain technique is applied to coefficients obtained as the result of transformation of either a whole audio or the frame of the audio. Some well-known and conventional transform domain techniques are discrete wavelet transform (DWT) [4], discrete cosine transform (DCT) [5], and fast fourier transform (FFT) [6]. Pandey et al [3] presented a method that uses the pseudo-random gray sequence property.…”
Section: Related Researchmentioning
confidence: 99%
“…Kaur et al [4] suggested a method based on a mathematical model by using features such as energy, short time energy, and zero cross means, but robustness against some attacks is quite low. Tsai et al [5] proposed a watermarking method based on energy averaging. However, the data payload of this method is not reported there.…”
Section: Related Researchmentioning
confidence: 99%
See 3 more Smart Citations